(untitled) (Foro de Educacion, 2024)
The question of whether school is a place for social transformation or not is a central issue to modern educational thought, particularly in the last decades of the twentieth century. «Theories of resistance» of the 80’s and 90’s aimed to show the transformative potential of schooling through the development of a critical pedagogy, in clear response to the so called «theories of reproduction», which in the 70›had denounced the role played by school in capitalism. This article aims to make a review of this discussion and, particularly, the antagonistic form in which it has been developed, from a materialist perspective. To that end, main classics of both group of theories will be analyzed identifying that, although they seem antagonist, they coincide on one central point: the belief that capitalist social relations are imposed externally to the subject, to a supposal free subjectivity. While «theories of reproduction» argue that such domination can only be faced through class struggle, which can only be given outside school, «theories of resistance» argue that struggle may be developedin the ideological sphere within schooling. The premise of this article is that such external imposition is an appearance product of the alienated character of our consciousness, and does not allow to analyze that social relations, far from being imposed to our free will, are developed by us to organize social work. To transcend these appearances, a process of recognition of the general determinations of education in capitalism will be developed, in order to enable us to overcome a binary logic between reproduction and transformation, and think social transformation as part of the process of social organization itself.